2021
DOI: 10.3389/fmicb.2021.638609
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Understanding of Candida albicans Biofilm Formation and Approaches for Its Inhibition

Abstract: In recent years, the demand for novel antifungal therapies has increased several- folds due to its potential to treat severe biofilm-associated infections. Biofilms are made by the sessile microorganisms attached to the abiotic or biotic surfaces, enclosed in a matrix of exopolymeric substances. This results in new phenotypic characteristics and intrinsic resistance from both host immune response and antimicrobial drugs. Candida albicans biofilm is a complex association of hyphal cells that are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 186 publications
(202 reference statements)
1
60
0
Order By: Relevance
“…Dissemination can lead to systemic candidiasis in severely immunocompromised patients that is associated with high mortality rates [reviewed in ( Nobile and Johnson, 2015 )]. The central role of biofilms in disease has prompted new approaches in antifungal drug design that target initiation of biofilm formation and disruption of mature biofilms ( Pierce and Lopez-Ribot, 2013 ; Atriwal et al., 2021 ).…”
Section: Parasex Inside C Albicans Biofilmsmentioning
confidence: 99%
“…Dissemination can lead to systemic candidiasis in severely immunocompromised patients that is associated with high mortality rates [reviewed in ( Nobile and Johnson, 2015 )]. The central role of biofilms in disease has prompted new approaches in antifungal drug design that target initiation of biofilm formation and disruption of mature biofilms ( Pierce and Lopez-Ribot, 2013 ; Atriwal et al., 2021 ).…”
Section: Parasex Inside C Albicans Biofilmsmentioning
confidence: 99%
“…One of the major problems related to the efficacy of antibiotics is the creation of biofilm by bacteria and fungus [41,42]. Biofilm promotes the propagation of these organisms and helps them to be more resistant to pharmacological treatments [43,44]. It has also been demonstrated that the formation of the biofilm plays a key role in catheter-associated infection [45].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are more complex structures that protect their cells from environmental influences, but some biofilm properties, such as the embedding of cells in extracellular matrix (ECM) and their connection by extracellular fibers, hinder some experimental manipulations. Biofilm research has become increasingly important in recent years, mainly because of biofilm key role in fungal infections [13] , [14] , [15] . Colonies are less structured and consist of precisely localized cell subpopulations that evolve synchronously over time, making specific cell types amenable to separation, relocalization, and other manipulation techniques.…”
Section: Introductionmentioning
confidence: 99%